2018
DOI: 10.1039/c8md00151k
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into the interaction of Hsp90 with allosteric inhibitors targeting the C-terminal domain

Abstract: Unique to targeting the C-terminal domain of Hsp90 (C-Hsp90) is the ability to uncouple the cytotoxic and cytoprotective outcomes of Hsp90 modulation. After the identification of novobiocin as a C-Hsp90 interacting ligand a diverse gamut of novologues emerged, from which KU-32 and KU-596 exhibited strong neuroprotective activity. However, further development of these ligands is hampered by the difficulty to obtain structural information on their complexes with Hsp90. Using saturation transfer difference (STD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The amino acid residues Glu489 (Glu497 in Hsp90α), Ser669 (Ser677 in Hsp90α), and Leu664 (Leu672 in Hsp90α) that interact with 9i ( Figure 7 ) also form ionic interactions and hydrogen bonds with bisphenol derivative [ 50 ] and novobiocin analogues [ 30 ]. In addition, 9i forms hydrophobic contacts with Ile486 (Ile494 in Hsp90α) ( Figure 7 ), which was identified by protein NMR spectroscopy studies as important for the binding of novobiocin analogues KU-32 and KU-596 to Hsp90 CTD [ 51 ]. However, this binding site does not overlap with that of the peptide-based inhibitor AX [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid residues Glu489 (Glu497 in Hsp90α), Ser669 (Ser677 in Hsp90α), and Leu664 (Leu672 in Hsp90α) that interact with 9i ( Figure 7 ) also form ionic interactions and hydrogen bonds with bisphenol derivative [ 50 ] and novobiocin analogues [ 30 ]. In addition, 9i forms hydrophobic contacts with Ile486 (Ile494 in Hsp90α) ( Figure 7 ), which was identified by protein NMR spectroscopy studies as important for the binding of novobiocin analogues KU-32 and KU-596 to Hsp90 CTD [ 51 ]. However, this binding site does not overlap with that of the peptide-based inhibitor AX [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, expression of the Myc oncoprotein can promote the formation of an Hsp90 protein network that imparts sensitivity to select N-terminal inhibitors (Rodina, et al, 2016). Moreover, using saturation transfer distance NMR spectroscopy to analyze the interaction of KU-596 with Hsp90 has identified that it functions as an allosteric modulator that can elicit global conformational changes that can extend to the N-terminal region in the Hsp90 dimer and potentially affect co-chaperone interactions (Kumar Mv, et al, 2018). However, additional work is needed to determine if diabetes can similarly induce changes in protein partners that interact with Hsp90 and affect the pharmacology of C-terminal Hsp90 inhibitors such as KU-596.…”
Section: Discussionmentioning
confidence: 99%
“…The principal advantage of C-terminal inhibition over N-terminal inhibition is the lack of a heat shock response upon ligand binding at the C-terminus of Hsp90. The first compounds that clearly differentiated between the C-terminus of Hsp90 and DNA gyrase, and converted a well-established gyrase inhibitor into a selective Hsp90 inhibitor were initially reported by Donnelly and Blagg ( 2008 ), Matts et al ( 2011a ), Matts et al ( 2011b ), Garg et al ( 2016 , 2017a , b ), Hall et al ( 2016 ), Khandelwal et al ( 2016 ), and Kumar MV et al ( 2018 ). The first experimental-guided computational prediction and mapping of hidden allosteric sites in Hsp90 combined NMR analysis, proteolytic fingerprinting and photoaffinity labeling with multiscale modeling of Hsp90 interactions and docking (Matts et al, 2011a , b ).…”
Section: Exploiting Allosteric Mechanisms and Cryptic Binding Sites Fmentioning
confidence: 99%